The Neotropical species of the genera Pseudespeson Lecoq, 1994 and Espeson Schaufuss, 1882 (Coleoptera: Staphylinidae: Osoriinae). - Irmler, Ulrich (Contributions to Entomology = Beiträge zur Entomologie, 2012)
A review of the Neotropical species of the genera Pseudespeson Lecoq, 1994 and Espeson Schaufuss, 1882 has been performed. Whereas no new species could be added to the genus Pseudespeson Lecoq, 1994, six new species were found in the genus Espeson Schaufuss, 1882. These are: E. adisi n. sp., E. dybasi n. sp., E. franiae n. sp., E. hermani n. sp., E. pecki n. sp., and E. simplex n. sp. One species, E. lenkoi Scheerpeltz, 1970, is synonymised with E. moratus Schaufuss, 1882. Thus, in total, 2 species of Pseudespeson Lecoq, 1994, and 13 species of Espeson Schaufuss, 1882 are actually known from Central and South America including the West Indies. Keywords Osoriinae, Espeson, Pseudespeson, new species, Neotropics. Nomenclatural Acts adisi Irmler, 2012 (Espeson), spec. nov. dybasi Irmler, 2012 (Espeson), spec. nov. franiae Irmler, 2012 (Espeson), spec. nov. hermani Irmler, 2012 (Espeson), spec. nov. lenkoi Scheerpeltz, 1969 (Espeson), syn. nov. of Espeson moratus Schaufuss, 1882 pecki Irmler, 2012 (Espeson), spec. nov. simplex Irmler, 2012 (Espeson), spec. nov.